1987
DOI: 10.2307/1939893
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analyses of Carbon Dynamics in Native and Cultivated Ecosystems

Abstract: Plant productivity, litter decomposition rates, and soil organic matter accumulation for winter wheat and for unbroken tallgrass prairie in Central Missouri were analyzed and compared. As measured in this 3-yr study, annual production of dry matter above- and belowground for the cultivated system averaged slightly higher than that for the natural vegetation burned every 3-4 yr. Prairie was characterized by greater year-to-year fluctuation of productivity, which in some years exceeded productivity of the cultiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
65
2

Year Published

1991
1991
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 176 publications
(75 citation statements)
references
References 37 publications
8
65
2
Order By: Relevance
“…Additionally, it has been reported that the annual SCE values in wheat fields were 640 g C m À2 in Missouri, United States (Buyanovsky et al 1987) and 579 g C m À2 in the Tibetan Plateau (Shi et al 2006). The annual SCE in this study (891.89 g C m À2 in 2006 and 865.08 g C m À2 in 2007) was slightly higher than those values.…”
Section: Discussioncontrasting
confidence: 63%
See 1 more Smart Citation
“…Additionally, it has been reported that the annual SCE values in wheat fields were 640 g C m À2 in Missouri, United States (Buyanovsky et al 1987) and 579 g C m À2 in the Tibetan Plateau (Shi et al 2006). The annual SCE in this study (891.89 g C m À2 in 2006 and 865.08 g C m À2 in 2007) was slightly higher than those values.…”
Section: Discussioncontrasting
confidence: 63%
“…The annual SCE in this study (891.89 g C m À2 in 2006 and 865.08 g C m À2 in 2007) was slightly higher than those values. This difference in SCE might have been due to higher residue input (about 5.7 t ha À1 in our study vs 3.9 t ha À1 in Missouri; Buyanovsky et al 1987) and differences in climate (temperate climate in our study vs alpine climate in the study conducted by Shi et al 2006). In a recent report, the average SCE in wheat fields near our site measured by an Li-8100 in 2008 was 2.1 lmol m À2 s À1 from March to June (Gao et al 2009).…”
Section: Discussionmentioning
confidence: 52%
“…The current study does not contradict the general positive response of SR to temperature, but indicates that temperature is not necessarily the single most important factor. Soil respiration is a net flux derived from several different processes, and changes occurring in any single process can be masked by opposite changes in another (Buyanovsky and Wagner 1995). During the growing season, NPP and biomass changed rapidly on several days (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Farahani et al 1998). Unfortunately, it has often been reported that such agricultural practices on Chernozem soils had accelerated organic matter decomposition (Buyanovsky et al 1987;Srivastava and Meyer 1998;Mikhailova et al 2000;Karbozova-Saljnikov et al 2004).…”
mentioning
confidence: 99%